Akibat Hukum Perbuatan Wanprestasi Dalam Perjanjian Hutang-Piutang - I Wayan Bandem; Wayan Wisadnya; Timoteus Mordan (Universitas Mahendradatta, 2020)
Accounts payable is a practice of lending and borrowing generally in the formof money as the object of the loan that is done by someone with another person made inan agreement. The agreement itself has been regulated in the provisions of the Civil Code(Civil Code). In civil law the agreement has been regulated regarding the rights andobligations of the parties making the agreement. The party that gives the loan is calledthe creditor while the party that receives the loan is called the debtor. Creditors areentitled to fulfillment of achievements while debtors must carry out their achievements.However, in reality the legal relationship between creditors and debtors, especiallyregarding agreements, is often problematic so that defaults arise. Default is a negligentevent where a person does not carry out his performance or does not fulfill his obligationsaccordingly, thus causing harm to one party. This research is entitled